Study of the phytoplankton plume dynamics off the Crozet Islands (Southern Ocean): A geochemical‐physical coupled approach. Issue 4 (10th April 2014) - Sanial, Virginie; van Beek, Pieter; Lansard, Bruno; d'Ovidio, Francesco; Kestenare, Elodie; Souhaut, Marc; Zhou, Meng; Blain, Stéphane
Abstract The Crozet Archipelago, in the Indian sector of the Southern Ocean, constitutes one of the few physical barriers to the Antarctic Circumpolar Current. Interaction of the currents with the sediments deposited on the margins of these islands contributes to the supply of chemical elements—including iron and other micro‐nutrients—to offshore high‐nutrient, low‐chlorophyll (HNLC) waters. This natural fertilization sustains a phytoplankton bloom that was studied in the framework of the KEOPS‐2 project. In this work, we investigated the time scales of the surface water transport between the Crozet Island shelves and the offshore waters, a transport that contributes iron to the phytoplankton bloom. We report shelf‐water contact ages determined using geochemical tracers (radium isotopes) and physical data based on in situ drifter data and outputs of a model based on altimetric Lagrangian surface currents. The apparent ages of surface waters determined using the three independent methods are in relatively good agreement with each other. Our results provide constraints on the time scales of the transport between the shelf and offshore waters near the Crozet Islands and highlight the key role played by horizontal transport in natural iron fertilization and in defining the extension of the chlorophyll plume in this HNLC region of the Southern Ocean.